Dilution of Urine Followed by Adulteration in an Attempt to Deceive the Laboratory. Issue 1 (6th September 2018) - Feldhammer, Matthew; Saitman, Alec; Nguyen, Ly; Milstid, Bryan
Abstract: Adulteration of samples submitted for toxicological analyses can present unique challenges to non-forensic clinical laboratories. With the number of overdose-related deaths expected to surpass 60, 000 in 2018, it is incumbent on all members of the healthcare team to be active participants in curbing opioid dependence and identifying prescription drug misuse and diversion. Recently published guidelines have sought to provide guidance to laboratories overseeing prescription drug-monitoring programs. We present a case of sample adulteration in an attempt to conceal prescription non-compliance. The patient possessed only an active prescription for hydrocodone but on initial antibody-based screening the sample tested positive for benzodiazepines and oxycodone in addition to opiates. Active communication between the pain management clinic and the clinical laboratory alerted staff to conduct a more thorough investigation including sample validity testing, analyses of paired serum specimens by liquid chromatography tandem mass spectrometry. Analyses revealed the patient submitted a dilute urine specimen with a crushed hydrocodone pill inside in an attempt to hide prescription non-compliance. Previous screenings had been consistent with the medication list raising the question of whether this was an isolated incident or the patient had simply been more successful in manipulating specimens in the past. This case highlights the need for good communication among all members of the healthcare team and the widespread implementation of specimen validity testing for any laboratory that receives samples from pain clinics.